2004
DOI: 10.1002/bit.20318
|View full text |Cite
|
Sign up to set email alerts
|

Causes of proteolytic degradation of secreted recombinant proteins produced in methylotrophic yeastPichia pastoris: Case study with recombinant ovine interferon-?

Abstract: It was observed that during fermentative production of recombinant ovine interferon-tau (r-oIFN-tau) in Pichia pastoris, a secreted recombinant protein, the protein was degraded increasingly after 48 h of induction and the rate of degradation increased towards the end of fermentation at 72 h, when the fermentation was stopped. Proteases, whose primary source was the vacuoles, was found in increasing levels in the cytoplasm and in the fermentation broth after 48 h of induction and reached maximal values when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 161 publications
(117 citation statements)
references
References 28 publications
4
110
0
3
Order By: Relevance
“…If so, the cell must sense a change in its metabolic state and either down-regulate recombinant protein synthesis downstream from transcription or up-regulate proteolytic pathways. The latter event is supported by Sinha et al (2004), who demonstrated that protease levels increased late in the production phase. Down-regulation of recombinant proteins has not been tested in P. pastoris, but work completed with the methylotrophic yeast H. polymorpha showed that the expression of E. coli β-galactosidase resulted in down-regulating the H. polymorpha AOX1 homolog methanol oxidase, and subse quently, β-galactosidase (Velkov et al 1999).…”
Section: Discussionmentioning
confidence: 75%
“…If so, the cell must sense a change in its metabolic state and either down-regulate recombinant protein synthesis downstream from transcription or up-regulate proteolytic pathways. The latter event is supported by Sinha et al (2004), who demonstrated that protease levels increased late in the production phase. Down-regulation of recombinant proteins has not been tested in P. pastoris, but work completed with the methylotrophic yeast H. polymorpha showed that the expression of E. coli β-galactosidase resulted in down-regulating the H. polymorpha AOX1 homolog methanol oxidase, and subse quently, β-galactosidase (Velkov et al 1999).…”
Section: Discussionmentioning
confidence: 75%
“…In a first attempt, we tried to disrupt the gene encoding vacuolar protease B (PrB) in P. pastoris strain GS115. Protease B is a serine protease of the subtilisin family and was postulated to be secreted by P. pastoris (38). A gene encoding the putative P. pastoris PrB (PRB) was cloned from a P. pastoris genomic library as described in Materials and Methods.…”
Section: Resultsmentioning
confidence: 99%
“…During the production of heterologous proteins in a highcell-density process, some of the secreted heterologous proteins produced by P. pastoris were found to be subjected to substantial proteolysis (21,22,38). The major store of proteolytic activity in yeasts is located within the lumen of the vacuolar compartment (23), and previous reports disclosed that the proteolytic degradation of secreted recombinant proteins in P. pastoris was due to the release of proteases in the culture medium caused by cell lysis (27,38).…”
Section: Discussionmentioning
confidence: 99%
“…Combination of high density culture and small percentage cell lysis in the media may cause some proteins rapidly degraded. The protease such as proteinase A and proteinase B, carboxylpeptidase and aminopeptidase are major known proteases that induce protein degradation in P. Pastoris [8]. Several strategies to inhibit proteolysis activity have been reported, such as protein engineering [9], optimization of fermentation parameters (pH, temperature and growth rate), modification of culture media composition (rich media, additional amino acid or peptone, lowering salt concentration as well as soytone addition) and the use of protease deficient strain [10].…”
Section: Resultsmentioning
confidence: 99%